2013
DOI: 10.1177/0733464813490247
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Health-Related Quality of Life Among Korean Immigrant Elders

Abstract: Health-related quality of life (HRQOL) is a key clinical outcome, particularly for individuals with chronic conditions such as hypertension (HTN). While no previous research has examined contributors to HRQOL among Asian Americans in the United States, this study was conducted to identify correlates of HRQOL in hypertensive Korean immigrant elders (≥ 60 years of age) to address the gap. A total of 440 Korean elders with HTN participated in the study. The hierarchical regression model for HRQOL explained 32.8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…One study that was conducted in 2009 in Chongqing found that the relationship with family or friends could influence health related quality of life among hypertensive patients [32]. It was also proven that lower social support was associated with poorer health related quality of life among individuals with chronic conditions, such as hypertension among Korean American patients [33]. Family support played an important role in hypertension treatment compliance [34], and patients may derive HRQoL benefits from the emotional support [35].…”
Section: Discussionmentioning
confidence: 99%
“…One study that was conducted in 2009 in Chongqing found that the relationship with family or friends could influence health related quality of life among hypertensive patients [32]. It was also proven that lower social support was associated with poorer health related quality of life among individuals with chronic conditions, such as hypertension among Korean American patients [33]. Family support played an important role in hypertension treatment compliance [34], and patients may derive HRQoL benefits from the emotional support [35].…”
Section: Discussionmentioning
confidence: 99%
“…Depression is a common mental disorder and a major contributor to the overall global burden of diseases, especially in women [22]. Recent studies have consistently emphasized the importance of mental health interventions in relieving depression, especially for improving HRQOL in older immigrants [22,23]. In a study of Lee et -Chinese male and female immigrants [24], depression was also the strongest predictor of HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also suggests that women aged 60 years and older tend to report lower QoL than men (Lee et al, 2015;Pérez-Ros et al, 2018;Setiati et al, 2011). Future studies with more balanced samples should therefore address gender differences in terms of FoF and QoL.…”
Section: Strengths and Limitationsmentioning
confidence: 99%